Sex-specific associations between systemic autoantibodies and allergic sensitization or allergic disease – results from a population-based study - Linseisen, J.; Laichinger, C.; Kling, E.; Hoffmann, R.; Rohm, F.; Meisinger, C. (Frontiers in Immunology, 2026)
ObjectiveSo far, knowledge of determinants of the presence of systemic autoantibodies (AABs) in the population is limited. Here, we investigated possible associations between serum AABs and allergies, using data on allergic sensitization and diagnoses of allergic diseases.MethodsIn 331 participants of a population-based study, 5 humoral systemic AABs and 7 AAB screening tests were analyzed. Allergic sensitization was characterized by specific IgE concentrations in serum samples (CAP class ≥ 2); additionally, self-reported diagnoses of allergic diseases were used as exposure variables. Multivariable adjusted logistic regression models were applied to explore the association with AAB test positivity; all analyses were stratified by sex. In a sensitivity analysis, AAB test results were defined as non-normal and normal.ResultsIn 46.2% and 37.1% of female and male study participants, respectively, at least one positive AAB test was identified. Allergic sensitization was observed in 23.8% and 29.7% of female and male participants, while 26.2% and 9.3% reported at least one diagnosis of allergic disease, respectively. Positive associations between allergic sensitization and serum AABs were identified in women for rheumatoid factor (RF), antinuclear antibodies (ANA), and at least one positive AAB test; in men, there was some indication for an association with anti-neutrophil cytoplasmic antibody (ANCA) positivity. Self-reported diagnosis of allergic diseases was not significantly associated with the AAB positivity.ConclusionIn this population-based group of adults, there is evidence for an association between allergic sensitization and systemic AABs, almost exclusively in women. Large prospective studies are needed for confirmation and further investigation of individual AABs.